Quality of life and subjective well-being in undergraduate students - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
The study designed to investigate whether the quality of life and its four domains (physical health, psychological health, social relationships and environment) are significant predictors of subjective well-being and also to examine the quality of life in terms of gender, socio-economic level, the number of sibling, living environment, mother education level and father education level. The study was carried out with undergraduate students in German, French and English Language Teaching Departments and Primary Education Department. Subjective Well-Being Scale (Tuzgol Dost, 2004) and WHOQOL-BREF that was adapted to Turkish by Eser, Fidaner, Fidaner, et al. (1999) were used to collect data. Data were analyzed by using t-test, One Way ANOVA and stepwise regression analysis. Results revealed that quality of life (overall) and psychological health, social relationships and environment domains of quality of life predicted subjective well-being positively whereas physical health domain did not predict subjective well-being. In addition to this, significant difference was found in quality of life scores in terms of socio-economic level. (c) 2011 Published by Elsevier Ltd. Open access under CC BY-NC-ND license.
Keywords: Quality of life; subjective well-being; undergraduate student; psychological health